2017
DOI: 10.15604/ejef.2017.05.03.010
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Arab Spring Effect on Economic Growth in the Middle East Countries: Structural Break Panel Data Analysis

Abstract: Civil commotions that are started in December, 2010 and named as "Arab Spring" had been spread to Middle East countries and had also brought with it economic and political crises. Many economic, social and political factors that are mostly structural had been effective on starting this process. In this research, influence of Arab Spring on economic growth had been investigated with the help of cross-sectional dependency and structural break unit root test in five Middle East countries by using annual data in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Especially in panel data analysis, there are only a couple of studies have been carried out under this theme (Mironov & Konovalova, 2019;Itoh et al, 2016). One of the significant studies in this area is "The Influence of Arab Spring Effect on Economic Growth in the Middle East Countries' by Beser & Kilic (2017). They discussed how the Arab Spring affects five (5) Middle East countries in terms of their political and economic condition.…”
Section: Structural Breaks and Economic Developmentmentioning
confidence: 99%
“…Especially in panel data analysis, there are only a couple of studies have been carried out under this theme (Mironov & Konovalova, 2019;Itoh et al, 2016). One of the significant studies in this area is "The Influence of Arab Spring Effect on Economic Growth in the Middle East Countries' by Beser & Kilic (2017). They discussed how the Arab Spring affects five (5) Middle East countries in terms of their political and economic condition.…”
Section: Structural Breaks and Economic Developmentmentioning
confidence: 99%
“…Aisen and Veiga (2008) showed similar results and reported that the volatility in the inflation rate is highly related to political instability, in the same context, Aisen and Veiga (2013) show that the political risk influences the growth level of the country economy and affect negatively the banks performance by decreased capital accumulation. Beser and Kilic (2017) reported that the Arab Spring succeeded to effectively bring structural changes with regards to economic, social and political factors to many countries in the region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…They contend that the relationship between FD and EG is contingent upon country-specific variables such as income level, labour force, population, and the developmental stage of the country (whether it is developed, developing, or underdeveloped). Additionally, the political environment of the country and macro-level factors, such as global market share, the flow of foreign direct investments, and global economic downturns, also play a role in this nexus (Benczur et al, 2019;Doumbia, 2016;Asteriou & Spanos, 2019;Ruiz, 2018;Beser & Kilic, 2017).…”
Section: Introductionmentioning
confidence: 99%